2020
DOI: 10.3390/ijms21186919
|View full text |Cite
|
Sign up to set email alerts
|

Dim Light at Night Disturbs Molecular Pathways of Lipid Metabolism

Abstract: Dim light at night (dLAN) is associated with metabolic risk but the specific effects on lipid metabolism have only been evaluated to a limited extent. Therefore, to explore whether dLAN can compromise lipid metabolic homeostasis in healthy individuals, we exposed Wistar rats to dLAN (~2 lx) for 2 and 5 weeks and analyzed the main lipogenic pathways in the liver and epididymal fat pad, including the control mechanisms at the hormonal and molecular level. We found that dLAN promoted hepatic triacylglycerol accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…Here, we explored a potential circadian-dependent immunomechanism that can link dLAN to negative health consequences. Indeed, recently we reported dLAN-induced health risks by increased hepatic lipid accumulation in dLANexposed rats (24). In the current study, we tested the hypothesis that chronic exposure to low-intensity light at night (~2 lx) compromises the circadian system, leading to disturbances in the daily variation of circulating immune cells and leukocyte movement into the renal cortex under homeostatic conditions.…”
Section: Introductionmentioning
confidence: 88%
“…Here, we explored a potential circadian-dependent immunomechanism that can link dLAN to negative health consequences. Indeed, recently we reported dLAN-induced health risks by increased hepatic lipid accumulation in dLANexposed rats (24). In the current study, we tested the hypothesis that chronic exposure to low-intensity light at night (~2 lx) compromises the circadian system, leading to disturbances in the daily variation of circulating immune cells and leukocyte movement into the renal cortex under homeostatic conditions.…”
Section: Introductionmentioning
confidence: 88%
“…The altered body mass in mice was predominantly explained by the increased daytime food intake ( Fonken et al, 2010 ). The daily pattern of food intake was altered also in rats, but without the increased body weight and fat mass ( Stenvers et al, 2016 ; Okuliarova et al, 2020 ; Okuliarova et al, 2022 ). These latter results from rats are in line with our current study, and we suggest that this species differences can be caused either by differences in light sensitivity or the study designs, for instance the different photoperiods used (14:10 LD cycle in mice and 12:12 LD cycle in rats).…”
Section: Discussionmentioning
confidence: 99%
“…In Swiss Webster mice, exposure to 5 lux during the dark-time resulted in the development of obesity accompanied by elevated daytime food intake and the impairment of glucose tolerance ( Fonken et al, 2010 ; Fonken et al, 2013 ). In rats, similar lighting conditions did not affect body weight, but did disturb the circadian control of sleep ( Stenvers et al, 2016 ) and deposition of lipids to the liver ( Rumanova et al, 2019 ; Okuliarova et al, 2020 ). In our recent study, we showed that dim ALAN suppresses daily rhythms of clock genes and vasopressin in the central oscillator and resulted in altered rhythms in hormonal outputs, and food and water intake ( Okuliarova et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid metabolism is entwined with the circadian machinery, and its alterations are closely associated with circadian disruption [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. One factor that causes deterioration in circadian rhythms is glaucomatous damage to retinal ganglion cells (RGCs), which compromises light perception and signal transduction to the master clock (suprachiasmatic nuclei in the brain).…”
Section: Introductionmentioning
confidence: 99%
“…RGC damage was found to be associated with disrupted local [16,17] and systemic [18][19][20][21] circadian rhythms, as well as sleep [22,23]. Circadian rhythms of lipid metabolism are modulated by light and food [5][6][7][8][9][10][11][12][13][14][15]. Furthermore, light and the extent of the day-night intensity differences modulate chronotype, sleep parameters, and circadian alignment [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%